Fresno County Bar Association Sponsored Fresno Courthouse Historical Display Case - Watkins, Howard::::::::: (1989)
Dignitaries at opening of display: Fresno County Bar Association Historian Howard Watkins, ?, ?, ? ?, Robert Wash;, ?, Marian Mosely, Val Weston, ?, Vernon Conrad, County Supervisor Deran Koligian, ?, Judge Stephen Henry and Judge James Thaxter